MARITIME EVENT RISK MANAGEMENT AND LOCAL ENTREPRENEURIAL RESILIENCE: EVIDENCE FROM THE SEA EAGLE BOAT RACE - Arina Luthfini Lubis; Andri Wibowo; Yudha Wardani; Ziqra Putra Ilham (RADJA PUBLIKA, 2026)
This study examines the implementation of risk management in the Batam International Sea Eagle Boat Race 2025 and its impact on local entrepreneurial resilience in Belakang padang, Batam. As a maritime sport tourism event involving international participants and large numbers of visitors, effective risk management is essential to ensure event safety, operational continuity, and economic benefits for local communities. This research employed a qualitative case study approach using interviews, observations, documentation, and literature review. Data were analyzed based on the ISO 31000:2018 framework, covering communication and consultation, risk identification, risk analysis, risk treatment, and monitoring and review processes. The findings indicate that risk management implementation was generally effective, particularly in stakeholder coordination, risk identification, and mitigation measures. Major risks identified included participant safety, visitor congestion, and limited SME bazaar space; however, these risks were successfully managed, allowing the event to proceed safely and without significant incidents. The study further reveals that effective risk management contributed to creating a secure business environment, which enhanced SME preparedness, adaptive capacity, and entrepreneurial resilience. These findings suggest that risk management plays a strategic role in ensuring successful maritime event operations, also in supporting sustainable tourism development and strengthening local economic resilience through community-based entrepreneurship.